Study on the Composite Structure of Aluminum Foam-Filled Thin-Walled Metal Tube to Reduce the Charge Overload inside the Projectile during the Penetration Process - Fudi Liang; Zengyou Liang; Dezhi Deng (Shock and Vibration)
When a projectile penetrates a target at high speed, the charge loaded inside the projectile usually bears a high overload, which will consequently severely affect its performance. In order to reduce the overload of the charge during the penetration process, the structure of the projectile was improved by adding two buffers at both ends of the charge. In this study, the mathematical expressions were first gained about the axial buffering force generated by the thin-walled metal tube, aluminum foam, and the composite structure of aluminum foam-filled thin-walled metal tube when they were impacted by the high-speed mass block through reasonable assumptions and stress analysis. During the experiment on the high-speed projectile penetrating reinforced concrete target, the acceleration curve of the charge and the projectile body were obtained. The results show that the maximum overload that the charge was subjected to during the launch and penetration process was significantly reduced, and the change in overload, which the charge was subjected to during the penetration process, was also less obvious.